Volatile organic compounds in the atmosphere - Hester, R. E.; Harrison, Roy M., 1948- (Issues in environmental science and technology ;, 1995)
Interest in volatile organic compounds (VOCs) as air pollutants has increased dramatically in recent years. This book covers a number of very topical issues concerning VOCs, including stratospheric ozone depletion due to CFCs, and the properties of alternative substances; the role of VOCs in the photochemical formation of lower atmosphere (tropospheric) ozone; and the problem of the direct toxicity of VOCs such as benzene and formaldehyde. This Issue reviews our current knowledge of VOCs, drawing upon the expertise of renowned experts and major national and international research programmes. It examines man-made and natural sources, as well as pathways and chemical reactions in the atmosphere. It also looks closely at the sources and concentrations of VOCs indoors, where humans are most likely to be exposed to them. Volatile Organic Compounds in the Atmosphere describes techniques used for the calculation of emissions inventories and strategies for control, and explores the many Government policy matters relating to VOCs. It provides readers with in-depth, clearly explained coverage of the many complex scientific and policy issues surrounding VOCs in the atmosphere.